MANGROVE PLANT DERRIS TRIFOLIATA- EVALUATION OF ANTIBACTERIAL PROPERTY - SUGANYA, R.; THANGARAJ, M. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
OBJECTIVE: Natural products such as plant extract, either as pure compounds or as standardized extracts, provide unlimited opportunities for new drug discoveries because of the unmatched availability of chemical diversity. Secondary metabolites from plants especially mangroves is traditionally being used widely as antimicrobials. Hence, present study was aimed to determine the antibacterial property of Derris trifoliata against Gram positive organism: Staphylococcus aureus; Gram negative organisms: Escherichia coli and Klebsiella pneumonia. METHODS: The Derris trifoliata leaves were collected, cleaned, shade dried and grounded into a crude powder. The methanol leaf extracts were isolated. The antibacterial assay of the leaf extracts was performed by Agar well Diffusion method [8, 9]. MIC and MBC of the isolated compounds were performed by broth dilution method [12]. RESULT: Â The methanol extracts of Derris trifoliata showed the highest bactericidal activity against the Staphylococcus aureus and Escherichia coli but not against Klebsiella pneumonia. CONCLUSION: This present study was conducted to prove the medicinal application of the mangroves especially Derris trifoliata. This can lead to the discovery of antibacterial properties of other mangroves and their pharmaceutical importance. Keywords: Derris trifoliata, mangrove, Staphylococcus aureus, Escherichia coli, antibacterial assay.